Code before Content? Brogrammer Culture in Games and Electronic Literature. - SALTER, ANASTASIA (Hyperrhiz)
Electronic literature exists at the intersection of the humanities, arts, and STEM: an acronym that itself defines a contested battleground of technical skills. The lack of diversity in STEM has received considerable scrutiny, and computer-related fields particularly suffer from a lack of diversity. Women earn only 18% of computer science degrees as of 2011 (Institute of Education Sciences 2012), and a self-study of the games industry found that women represent only 5% of programmers and 13% of designers (Gamasutra Salary Survey 2014). This has contributed to the rise of "brogrammer" culture in disciplines with strong computer science components, and with it a rhetorical collision of programming and hypermasculine machismo. Brogrammer culture is self-replicating: in technical disciplines, the association of code with masculinity and men's only spaces plays a pivotal role in reinforcing the status quo. Given this dramatic under-representation of women and nonbinary people in computer science disciplines, the privileging of code-driven and procedural works within the discourse of electronic literature is inherently gendered. The emergence of platforms friendly to non-coders (such as Twine) broadens participation in electronic literature and gaming spaces, but often such works are treated and labeled differently from code-driven and procedural works that occupy the same space. I argue that electronic literature communities must be aware of the gendered rhetoric and socialization surrounding code, and be vigilant against the tendency to value code (and, by extension, male-coded labor) over content when evaluating works in this form.